Biological maturity-associated variance in peak power output and momentum in academy rugby union players - Howard, S. M. A.; Cumming, S. P.; Atkinson, M.; Malina, R. M. (European Journal of Sport Science, 2016)
The study aimed to evaluate the mediating effect of biological maturation on anthropometrical measurements, performance indicators and subsequent selection in a group of academy rugby union players. Fifty-one male players 14-17 years of age were assessed for height, weight and BMI, and percentage of predicted mature status attained at the time of observation was used as an indicator of maturity status. Following this, initial sprint velocity (ISV), Wattbike peak power output (PPO) and initial sprint momentum (ISM) were assessed. A bias towards on-time (n = 44) and early (n = 7) maturers was evident in the total sample and magnified with age cohort. Relative to UK reference values, weight and height were above the 90th and 75th centiles, respectively. Significant (p = .01) correlations were observed between maturity status and BMI (r = .48), weight (r = .63) and height (r= .48). Regression analysis (controlling for age) revealed that maturity status and height explained 68% of ISM variance; however, including BMI in the model attenuated the influence of maturity status below statistical significance (p = .72). Height and BMI explained 51% of PPO variance, while no initial significant predictors were identified for ISV. The sample consisted of players who were on-time and early in maturation with no late maturers represented. This was attributable, in part, to the mediating effect of maturation on body size, which, in turn, predicted performance variables.